2016
DOI: 10.1002/ccd.26802
|View full text |Cite
|
Sign up to set email alerts
|

First North American experience with the transfemoral ACURATE‐neoTM self‐expanding transcatheter aortic bioprosthesis

Abstract: The present initial North American experience shows that the ACURATE-neo aortic bioprosthesis was safely and successfully implanted by transfemoral approach. The special design of this newer-generation device affords a stable and predictable implantation, while providing optimal hemodynamic performance with a relatively low rate of PPI. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
0
17
1
Order By: Relevance
“…Importantly, PVL was absent or trace in 92% of patients, 7.7% of patients showed mild PVL, 0.3% of patients moderate PVL and none presented with severe PVL. The Lotus Valve TM device seals the aortic annulus adjusting to the patient's anatomy with the mechanically expandable frame, and these results are equivalent or compare favorably to recent reports using different second-generation TAV devices (6,8,9,13,14). (15) showed that the independent predictors of mild/moderate PVL included the ratio of device area to annulus area, left ventricular outflow tract (LVOT) calcium volume, and annulus area.…”
Section: Acute Valve Performance and Paravalvular Sealingmentioning
confidence: 61%
See 1 more Smart Citation
“…Importantly, PVL was absent or trace in 92% of patients, 7.7% of patients showed mild PVL, 0.3% of patients moderate PVL and none presented with severe PVL. The Lotus Valve TM device seals the aortic annulus adjusting to the patient's anatomy with the mechanically expandable frame, and these results are equivalent or compare favorably to recent reports using different second-generation TAV devices (6,8,9,13,14). (15) showed that the independent predictors of mild/moderate PVL included the ratio of device area to annulus area, left ventricular outflow tract (LVOT) calcium volume, and annulus area.…”
Section: Acute Valve Performance and Paravalvular Sealingmentioning
confidence: 61%
“…Recent recommendations found that transfemoral TAVI, in comparison to SAVR, results in lower mortality and acute kidney injury at 2 years, and may reduce stroke rates (5). Over the past 15 years, several transcatheter devices have been tested and evolved to decrease access site complications with smaller profile delivery systems, decrease pacemaker rates, and avoid the risk of coronary obstruction and significant paravalvular leakage (PVL) (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…A coronary height less than 12 mm is a predictor for coronary obstruction, especially in narrow or porcelain aortic roots . The ACURATE‐ neo ™ is designed for infra‐coronary placement; the stabilization‐arches are opened in the ascending aorta while the upper‐crown and waist capture the native aortic leaflets toward the aortic annulus, consequently diminishing the risk for coronary ostia obstruction …”
Section: Discussionmentioning
confidence: 99%
“…The ACURATE‐ neo ™ with its ACURATE‐TF™ delivery system is well designed for horizontal aortic roots, an anatomical feature that has been traditionally considered a challenge for transfemoral TAVR procedures. Unlike other self‐expanding devices, the ACURATE‐ neo ™ is released from the aorta, following the “top‐to‐down” concept, rather than from the LVOT . Notably, the “V‐shape” of the device with the upper‐crown and stabilizers opened (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation